Root accumulation and efficient translocation of steroids in mangrove plants: Implications for an overlooked coastal reservoir - Ji-Xun Chen; Nian-Nian Wu; Shan Liu; Yuan Liu; Qin-Ge Zhou; Qing-Song Yang; Juan Ling; Xiao-Fang Huang; Yan-Kuan Tian; Chang-Gui Pan; Xiang-Rong Xu (Marine Pollution Bulletin, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

DNA methylome analysis reveals EjABCG23-mediated epigenetic regulation underlying fruit russeting in white-fleshed loquat - Kun Zhang; Yuying Ding; Rong Su; Chang Liu; Xuelian Li; Yang Wang; Yan Deng; Qiong Zhou; Xiaojun Chen; Yuxing Li; Qunxian Deng (Postharvest Biology and Technology, 2026)

Intensive anthropogenic activities control the spatiotemporal heterogeneity of river eutrophication at the watershed scale - Xihua Wang; Shunqing Jia; Y. Jun Xu; Chaomeng Dai; Nianqing Zhou; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Hydrology, 2026)

Exploring the potential of millets as the next-generation sustainable source of plant-based protein: A review - Rong Wei; Jiahong Wang; Jiakai Wang; Ting Bai; Fang Zhong; Zheng Yan; Sumei Zhou; Qun Shen; Dianzhi Hou (Journal of Cereal Science, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Burkholderia cepacia NB-13: Biocontrol efficacy and medium-driven metabolic regulation - Zhou Yin; Xiaoqin Li; He Guan; Dindi Tu; Xingyi Luo; Wancheng Hu; Fanqian Zhou; Menglong Li; Shulin Liu; Hui Li; Rong Song; Kailin Liu; et al. (Pesticide Biochemistry and Physiology, 2026)

A refined stratigraphic framework for the Tremadocian–Floian stage boundary (Lower Ordovician) in the North China Block - Xiang-Ri Chi; Guan-Zhou Yan; Mikael Calner; Fang-Yi Gong; Xiao-Cong Luan; Rong-Chang Wu (Palaeoworld, 2026)

Wenyang Yishen Tongluo prescription synergizes with bone marrow mesenchymal stem cells to alleviate rheumatoid arthritis via inhibiting IL-6 - Rong Su; Shiyun Yin; Lingli Gu; Weichao Liu; Weitian Yan; Weijian Zhou; Jiangyun Peng (Journal of Molecular Histology, 2026)

Escalating Antibiotic Inputs Alter Aquatic Plant Detritus Decomposition and Organic Carbon Mineralization: A Case Study of Gehu Lake, China - Jingyang Xu; Yue Ren; Yin Yan; Yuxuan Rong; Wenhui Tu; Tao Huang; Chuanqiao Zhou; Hideyuki Doi; Changchun Huang (Chinese Geographical Science, 2026)

PM2.5 exposure exacerbates cerebral infarction via HPG axis downregulation and pituitary lipid metabolism dysregulation in mice - Xin lv; Guanhui Pei; Lijuan Liu; Zhou zhou; Yicong Zhou; Binbin Wang; Chaoyue Meng; Ruomeng Chen; Qiang Yao; Ge Bai; Xuelin Wang; Minghan Zhao; et al. (NeuroToxicology, 2026)

Distribution of plutonium in a ternary system of water-colloid-bentonite: Implications for radionuclide migration - Yan Liu; Chun Zhang; Yu Wang; Hui Xu; Rong Gong; Jianzheng Zang; Jianbo Liu; Xiang Zhou (Journal of Contaminant Hydrology, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Association of phthalate exposure during early pregnancy with fetal growth and the effect modification by gestational stress - Nian Wu; Zhongmei Hu; Xinyi Xiao; Shimin Xiong; Xingyan Liu; Yan Xie; Rong Zeng; Kunming Tian; Xubo Shen; Yuanzhong Zhou; Yijun Liu (International Journal of Hygiene and Environmental Health, 2026)

Synergistic retrievals of leaf area index and leaf chlorophyll content in deciduous broadleaf forests from Sentinel-2 and Landsat - Haoqiang Zhou; Mingzhu Xu; Jing M. Chen; Xingchang Wang; Rong Shang; Rong Wang; Yulin Yan; Jun Wang (Remote Sensing of Environment, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Precise pH control and synergistic interaction of raw materials improve the quality of stewed beef: multi-omics analysis of tenderization mechanisms and flavor restructuring - Yan Shen; Zezhu Du; Jinya Dong; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Cheng Gong; Shikuan Zhao; Zhiyu Li; Lihui Yu; Rong Geng; Xiaocui Du; et al. (Food Chemistry, 2026)

Effects of recovered exogenous nitrogen addition on pilot-scale single-cell protein production from soybean soaking water - Hui Xu; Yingqiu Pu; Li Wang; Rong Huang; Yan Zhou (Bioresource Technology, 2026)

Design of sequential strongly convex programming algorithm for reentry trajectory planning - Yutang Li; Di Zhou; Zhen He; Songzhou Li; Siyuan Li; ChaoRan Yan; Rong Huang (Advances in Space Research, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Occurrence, composition profiles, and human exposure assessment of liquid crystal monomers in indoor dust from Wuxi, China - Yiyang Yao; Linlin Wu; Run Zhou; Xi Wang; Yan Gong; Rong Chen; Wenwei Liu (Environmental Pollution, 2026)

Intensive anthropogenic activities drive dynamic surface water-groundwater interactions: Implications for contaminant pathways at a catchment scale - Shunqing Jia; Xihua Wang; Y. Jun Xu; Chaomeng Dai; Nianqing Zhou; Zejun Liu; Boyang Mao; Qinya Lv; Xuming Ji; Chengming Luo; Yan Dai; Yanxin Rong (Journal of Contaminant Hydrology, 2026)

Risk assessment and environmental influencing factors of urinary polycyclic aromatic hydrocarbons metabolites in pregnant women in Zunyi, China - Jing Yang; Jing Jiang; Linfei Wu; Pei Xu; Nian Wu; Rui Yu; Yanling Xiao; Xingting Zheng; Rong Zeng; Yuanzhong Zhou; Yan Xie; Xubo Shen (Journal of Environmental Sciences, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Research on the fungi in dry-cured hams from different regions and exploration of new resources of flavor yeast - Wucong Zhou; Ai Zelin; Zilin Chen; Zhengyang Bao; Minxuan Shi; Chenghan Rong; Shuqing Yan; Xinzhu Zhang; Chunbao Li; Kai Shan (Food Research International, 2025)

Silencing aquaporin 1 inhibits autophagy to exert anti-rheumatoid arthritis effects in TNF-α-induced fibroblast-like synoviocytes and adjuvant-induced arthritis rats - Man-yu Zhang; Meng-qing Wang; Yan Huang; Sheng-long Gu; Meng-yuan Zhou; Ze-shan Xu; Ling-ling Li; Min Lv; Li Cai; Rong Li (Inflammation Research, 2025)

Hypocalcemia as biological mechanism responsible for prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) and anemia: Insights from Zunyi birth cohort - Lei Luo; Wenbi Yang; Haonan Zhang; Lei Bai; Zhongbao Chen; Lin Tao; Haiyan Wang; Shimin Xiong; Ruoxuan Li; Yijun Liu; Xingyan Liu; Yan Xie; et al. (Journal of Environmental Sciences, 2025)

FT-ICR MS and viral metagenomics reveal distinct mechanisms of lysogenic and lytic phage-driven DOM transformations in wastewater at formula-levels - Qi Wang; Jieqi Tian; Rong Zhang; Pengcheng Yan; Yali Niu; Guodong Zhang; Qiuling Ma; Jian Zhou; Ruigang Wang; He Guo; Tiecheng Wang (Chemical Engineering Journal, 2025)

Applications and challenges of modified algal biochar in environmental remediation - Yan Sun; Chunxiao Hao; Yongjie Wang; Huan Zhong; Song Zhou; Han Meng; Huan He; Pei Lei; Nan Rong (Chemical Engineering Journal, 2025)

Porous coordinated polymers/chitosan composite monolith with directional pore structure for highly efficient mono−/multi−/global phosphopeptide enrichment - Rong Li; Yan Wang; Dandan Zhou; Ruizhi Tang; Yangyang Bian; Shujuan Ma; Xingtai Qiu; Zichao Tang; Junjie Ou; Yehua Shen (Carbohydrate Polymers, 2025)

Neuroprotective Effects, Mechanisms of Action and Therapeutic Potential of the Kv7/KCNQ Channel Opener QO-83 in Ischemic Stroke - Huiran Zhang; Yanfei Tian; Yan Zhang; Yan Wang; Jinlong Qi; Xiangyu Wang; Yi Yuan; Rong Chen; Yupeng Zhao; Chang Liu; Najing Zhou; Lanxin Liu; et al. (Translational Stroke Research, 2025)

Hypoxic Natural Killer Cells-Derived HIF-1α-Containing Exosomes Inhibit Cellular Senescence and Apoptosis in Neurocytes to Ameliorate Alzheimer’s Disease by Eliminating Oxidative Damages - Yang Zhou; Yan Rong (Molecular Neurobiology, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Limited leaf thermal acclimation but higher tolerance in subtropical trees after 10-year translocation in Dinghushan biosphere reserve - Ting Wu; David T Tissue; Wei Su; Honglang Duan; Mark G. Tjoelker; Sachin G. Chavan; Shuyidan Zhou; Junfeng Yuan; Liang Fang; Mengxiao Yu; Shizhong Liu; Guowei Chu; et al. (Agricultural and Forest Meteorology, 2025)

Orchard variable rate spraying method and experimental study based on multidimensional prescription maps - Chenming Hu; Yu Ru; Shuping Fang; Zifan Rong; Hongping Zhou; Xianghai Yan; Mengnan Liu (Computers and Electronics in Agriculture, 2025)

Predicting single-cell protein production from food-processing wastewater in sequencing batch reactors using ensemble learning - Rong Huang; Hui Xu; Ezequiel Santillan; Di Jin; Zhenju Sun; David C. Stuckey; Yan Zhou; Stefan Wuertz; Shunzhi Qian (Bioresource Technology, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Theoretical insights into electrochemical CO2 reduction by Bi-based catalysts: single crystals versus mixed phases - Mengting Zhou; Hongxia Liu; Juntao Yan; Qingjun Chen; Huiping Zhao; Rong Chen; Lei Liu (Chemical Engineering Journal, 2025)

Au-isolated Pt active site with enhanced C-H bond activation ability for selective oxidation of polyol to hydroxyl acid - Xuewei Ding; Ying Liao; Rong Fan; Hao Yan; Xin Zhou; Xiang Feng; Xiaobo Chen; Hui Zhao; Yibin Liu; Chaohe Yang (Chemical Engineering Journal, 2025)

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Co-doping graphitic carbon nitride with Fe atoms and oxygen-containing functional groups for the efficient photo-Fenton degradation of sulfamethoxazole - Ruiyan Zhang; Cong Yan; Qinghua Yan; Congzhe Ren; Wen Zhang; Xiaozhe Song; Xuyang Li; Lei Chen; Fangyuan Zhou; Rong Xue; Feng Shi; Chongqing Xu (Journal of Water Process Engineering, 2025)

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

Water competition among coexisting plants in rock-dominated habitats of subtropical karst desertification - Lulu Cai; Kangning Xiong; Ziqi Liu; Yuan Li; Dayun Zhu; Yating Mu; Yi Chen; Rong Zhou; Xiaoyu Yan (Agriculture, Ecosystems & Environment, 2025)

Opposing island biogeographic effects of turnover and nestedness on beta-diversity of soil faunal communities between woodland and deforested grassland - Zengyan Li; Zengke Zhang; Anna Yang; Sufeng Pan; Junyong Zheng; Ling Mou; Wensheng Chen; Tian Zhang; Liyi Zhou; Wenhui You; David A. Wardle; En-Rong Yan (Applied Soil Ecology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Enhanced carrier separation and photocatalytic degradation of oxytetracycline via S-scheme MIL-53(Fe)/FeOCl heterojunction composites with peroxydisulfate activation - Wei Dong; Chunyan Du; Yin Zhang; Jiao Cao; Jingyi Jiang; Lu Zhou; Guanlong Yu; Yulv Zou; Huaiyuan Peng; Rong Yan; Yu Yang (Journal of Environmental Chemical Engineering, 2025)

Scalable deposition of SnO2 ETL via SALD for large-area inverted perovskite solar modules - Xuewei Jiang; Bin Shan; Geng Ma; Yan Xu; Xing Yang; Wenbin Zhou; Chenhui Li; Fan Yang; Rong Chen (Chemical Engineering Journal, 2025)

Revisiting bipolar membrane electrodialysis for the production of monoprotic organic acids with different p K a and Mw - Rong Zhou; Zhiguo Dong; Xixi Ma; Lili Xue; Jinxin Liu; Jinfeng He; Weiwei Li; Li Sun; Chuanrun Li; Haiyang Yan (Chemical Engineering Journal, 2025)

Model-based analysis for investigating the impact of tumor size, lymphocyte and neutrophil on the survival of breast cancer 4T1 tumor-bearing mice - Qing-yu Yao; Xin-yu Hou; Wei-zhe Jian; Tian-yu Wang; Ping-yao Luo; Jun-sheng Xue; Rong Chen; Tian-yan Zhou (Toxicology and Applied Pharmacology, 2025)

Evaluation of metagenomic next-generation sequencing (mNGS) combined with quantitative PCR: cutting-edge methods for rapid diagnosis of non-invasive fungal rhinosinusitis - Xiao Liu; Shaoqin Zhou; Rong Yan; Caifeng Xia; Ruoning Xue; Zhe Wan; Ruoyu Li; Sybren de Hoog; Sarah A. Ahmed; Quangui Wang; Yinggai Song (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

A Meta‐Analysis of Bycatch Mitigation Methods for Sea Turtles Vulnerable to Swordfish and Tuna Longline Fisheries - Hao Yan; Cheng Zhou; Eric Gilman; Jie Cao; Rong Wan; Fan Zhang; Jiangfeng Zhu; Liuxiong Xu; Liming Song; Xiaojie Dai; Siquan Tian (Fish and Fisheries, 2025)
Fisheries bycatch poses one of the most significant threats to sea turtles. Although various methodologies have been developed to mitigate sea turtle bycatch in swordfish and tuna longline fisheries, the effectiveness and interactions remain uncertain. In this study, we conducted a comprehensive meta‐analysis, encompassing 41 studies focused on sea turtles and 36 studies on tunas, swordfish and sharks, all derived from well‐controlled experimental research in swordfish and tuna longline fisheries. The objective was to systematically evaluate the relative effectiveness of species‐specific mitigation strategies for sea turtles, particularly examining the impact of circle hooks and fish bait as alternatives to conventional longline fishing practices. While a nuanced hierarchy, characterised by species‐specific patterns, was observed among the mitigation measures, circle hooks demonstrated great promise in reducing bycatch of loggerhead, olive ridley and leatherback turtles, with minimal impact on the catch rates of tuna, swordfish and sharks. We highlighted the broader applicability of fish bait in minimising sea turtle bycatch, noting that the effectiveness of bait may overlap with that of hooks, potentially making the additional benefits of the hooks less evident. The study also revealed regional variations in the effectiveness of these methods, emphasising the need for more detailed data collection. Given current data limitations that restrict extensive meta‐analyses, a series of small‐sample studies with promising innovations, exemplified by circle hooks with a wire appendage and blue‐white lights, necessitates in‐depth investigation and field tests.

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

New data on the Cambrian–Ordovician (Tremadocian) conodont biostratigraphy of Guizhou Province, Southwest China - Hadi Jahangir; Guan-Zhou Yan; Rong-Chang Wu; Ren-Bin Zhan (Palaeoworld, 2024)

Epidemiological and genomic analysis revealed the significant role of flies in dissemination of carbapenem-resistant Enterobacteriaceae (CRE) in China - Hongwei Zhou; Hanyu Wang; Kaichao Chen; Miaomiao Xie; Zelin Yan; Yanyan Zhang; Yuchen Wu; Dejun Liu; Juan Wang; Ning Dong; Chang Cai; Yongning Wu; et al. (Journal of Hazardous Materials, 2024)

Electrodialysis with ultrafiltration membrane for efficient isolation of oxymatrine from simulated eluent of traditional Chinese medicine - Zhiguo Dong; Rong Zhou; Zengqiang Wei; Yiwei Dong; Li Sun; Xixi Ma; Wenlong Liu; Qiuhua Li; Jinfeng He; Chuanrun Li; Haiyang Yan (Desalination, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

A joint-threshold Filippov model describing the effect of intermittent androgen-deprivation therapy in controlling prostate cancer - Aili Wang; Rong Yan; Haixia Li; Xiaodan Sun; Weike Zhou; Stacey R. Smith (Mathematical Biosciences, 2024)

Transfer from ciliate to zebrafish: Unveiling mechanisms and combined effects of microplastics and heavy metals - Yan Zhang; Caixia Wang; Ruiqi Jia; Hongan Long; Jianfeng Zhou; Gaojingwen Sun; YunLong Wang; Zhaoji Zhang; Xiaozhi Rong; Yong Jiang (Journal of Hazardous Materials, 2024)

Accumulation and depuration of 4,5-dihydro-KmTx2 from Karlodinium veneficum in the bivalves, Mercenaria mercenaria and Sinonovacula constricta - Yanrong Li; Rong Chen; Zhujun Zhu; Tong Mu; Zhaoshou Ran; Jilin Xu; Chengxu Zhou; Xiaojun Yan (Harmful Algae, 2024)

Genomic analysis of hypoxia-tolerant population of the Chinese mitten crab (Eriocheir sinensis) - Feng-yuan Yan; Yuan-feng Xu; Wen-rong Feng; Qing-hong He; Guo-an Hua; Wen-jing Li; Pao Xu; Jun Zhou; Yong-kai Tang (Fish & Shellfish Immunology, 2024)

The morphology of liquid CO2 hydrate films at different temperatures under saturation pressure - Yu-Jie Zhu; Yu Zhang; Yu-Zhou Chen; Yan Xie; Jin-Rong Zhong; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

Nomogram to Predict Good Neoangiogenesis After Indirect Revascularization Surgery in Patients with Moyamoya Disease: a Case–control Study - Kexin Yuan; Ke Wang; Haibin Zhang; Yunfan Zhou; Qiang Hao; Xun Ye; Xingju Liu; Qian Zhang; Yan Zhang; Rong Wang; Yuanli Zhao; Yahui Zhao (Translational Stroke Research, 2024)

Altered Function and Structure of the Cerebellum Associated with Gut–Brain Regulation in Crohn’s Disease: a Structural and Functional MRI Study - Yunfei Li; Yanling Zheng; Lan Rong; Yan Zhou; Zhen Zhu; Qian Xie; Zonghui Liang; Xiaohu Zhao (The Cerebellum, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Salient Object Detection in Optical Remote Sensing Images Based on Global Context Mixed Attention - Longquan Yan; Ruixiang Yan; Guohua Geng; Mingquan Zhou; Rong Chen (Journal of the Indian Society of Remote Sensing, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Differentiation of bone marrow mesenchymal stem cells into Leydig-like cells with testicular extract liquid in vitro - Rong Hua; Fang-Fang Liang; Fang-Qiang Gong; Hua Huang; Yi-Chen Xu; Min He; Yan-Hua Fang; Ya-Shu Wei; Wei-Wei Zhou; Arshad Mehmood; Yi Mo; Zhong Lin (In Vitro Cellular & Developmental Biology - Animal, 2024)

Analysis of mild and severe neonatal enterovirus infections in a Chinese neonatal tertiary center: a retrospective case-control study - Junshuai Li; Jingjing Xie; Min Zhang; Zhuojun Xiao; Fan Zhang; Weiqing Huang; Yong Zhou; Weiqun Yan; Rong Zhang; Xiaoming Peng (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Guided isolation of enantiomeric lignans from Cimicifuga heracleifolia Kom. by antioxidant activity and molecular networking - Yanwen Sun; Liyi Chen; Yan Zhou; Fei Han; Yifang Rong; Liqin Ding; Feng Qiu (Phytochemistry, 2024)

Overview of the recent advances in porcine epidemic diarrhea vaccines - Miao-Zhan Wei; Lan Chen; Rong Zhang; Ze Chen; Yan-Juan Shen; Bi-Jun Zhou; Kai-Gong Wang; Chun-Lan Shan; Er-Peng Zhu; Zhen-Tao Cheng (The Veterinary Journal, 2024)

Soybean inclusion reduces soil organic matter mineralization despite increasing its temperature sensitivity - Zhengjun Yan; Rong Jia; Jie Zhou; Kazem Zamanian; Yadong Yang; Kevin Z. Mganga; Zhaohai Zeng; Huadong Zang (Science of The Total Environment, 2024)

A specific module of ESCRT regulates STING activity termination by controlling STING degradation - Yuan Zhao; Chenxuan Zhou; Wenmin Tian; Yang Chen; Chongchong Zhao; Yan Li; Shixuan Wang; Yueguang Rong (Science Bulletin, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Hydrodynamic characteristics of frustum-type depressor for sampling midwater trawl - Zhiqiang Liu; Fuxiang Hu; Rong Wan; Yucheng Wang; Shaojian Guo; Hao Yan; Cheng Zhou (Ocean Engineering, 2024)

The environmental analysis and site selection of mussel and large yellow croaker aquaculture areas based on high resolution remote sensing - Lina Cai; Jie Yin; Xiaojun Yan; Yongdong Zhou; Rong Tang; Menghan Yu (Acta Oceanologica Sinica, 2024)

Suspended particulate matter <2.5 μm (SPM2.5) in shallow lakes: Sedimentation resistance and bioavailable phosphorus enrichment after sediment resuspension - Zhaona Zhou; Rong Yan; Xiao Liu; Ziying Xu; Jin Zhang; Qitao Yi (Science of The Total Environment, 2024)

Microplastics enhance nitrogen loss from a black paddy soil by shifting nitrate reduction from DNRA to denitrification and Anammox - Xiaofang Ma; Jun Shan; Yanchao Chai; Zhijun Wei; Chenglin Li; Ke Jin; Han Zhou; Xiaoyuan Yan; Rong Ji (Science of The Total Environment, 2024)

Effect of blending ratio on the compatibility and stability of konjac glucomannan/starch composite systems - Qian Zhang; Sicong Yan; Rong Zhou; Xu Yan; Peineng Zhu; Lingyun Chen; Fatang Jiang (Food Hydrocolloids, 2024)

Exposure levels and determinants of placental polybrominated diphenyl ethers in Chinese pregnant women - Yijun Liu; Yan Xie; Yingkuan Tian; Juan Liao; Derong Fang; Linglu Wang; Rong Zeng; Shimin Xiong; Xingyan Liu; Qing Chen; Ya Zhang; Hongyu Yuan; et al. (Environmental Research, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

Genome dosage alteration caused by chromosome pyramiding and shuffling effects on karyotypic heterogeneity, reproductive diversity, and phenotypic variation in Zea–Tripsacum allopolyploids - Yingzheng Li; Xu Yan; Mingjun Cheng; Zizhou Wu; Qiyuan Zhang; Saifei Duan; Yong Zhou; Huaxiong Li; Shipeng Yang; Yulin Cheng; Wansong Li; Lulu Xu; et al. (Theoretical and Applied Genetics, 2024)

Recognizing topological attributes and spatiotemporal patterns in spotted seals (Phoca largha) trophic networks based on eDNA metabarcoding - Yan Xu; Fei Huang; Mingliang Zhou; Rui Gu; Jie Zhu; Qiangqiang Rong; Yanpeng Cai (Frontiers in Marine Science, 2023)
Spotted seals, a protected species, face multifaceted threats to their habitat, which in turn impact the closely associated trophic networks. These threats will lead to irreversible structural variations within the ecosystem. Therefore, investigating the topological variability of trophic networks in spotted seals is important. Applying environmental DNA methods, field sample collection was conducted in 2021 during both the sea fishing moratorium period and the fishing period to decode fish diversity. Assessing the current status of fish resources by using the multivariate statistics approach. Applying dietary information establishes the spotted seals’ trophic network. Selecting 12 network indexes to analyze the spatiotemporal patterns of network topological attributes. As a result, about 51 families, and 76 genera species were identified. During the sea fishing moratorium and the fishing period, there are 12 and 18 different food resources available for spotted seals, respectively. The diversity index revealed that the FP had greater species richness and diversity than the SP. Comparatively, the Fishing period exhibited higher species richness and biodiversity, likely influenced by habitat heterogeneity and anthropogenic activities. Additionally, the topological features of networks reflected the high clustering coefficients (CC=0.35) and the proportion of omnivorous species (O≈60%), indicating that the network structure in this region tends to form higher trophic-level clustering patterns, which facilitate the formation of weaker interactions between clusters, enhancing the robustness of the network. The higher connectivity complexity index during the fishing period (SC=12.3) supported that the spotted seal’s trophic network was relatively more stable in this period. Thus, during the fishing period, it is crucial to pay more attention to the intensity of human fishing on mid-to-high trophic-level omnivorous fish resources to ensure the sustainability of these potential food resources for spotted seals. This comprehensive study achieved three key objectives: (a) utilizing eDNA to characterize fish diversity during distinct periods, (b) establishing trophic networks of spotted seals, and (c) discerning topological attributes and spatiotemporal patterns within the ecological network. Overall, this study can provide technical and data support for integrated ecological network management and propose suggestions for protecting and recovering spotted seals.

Mitochondria-related lncRNAs: predicting prognosis, tumor microenvironment and treatment response in lung adenocarcinoma - Qianhui Zhou; Jiali Xiong; Yan Gao; Rong Yi; Yuzhu Xu; Quefei Chen; Lin Wang; Ying Chen (Functional & Integrative Genomics, 2023)
Lung cancer is the most common type of malignant tumor that affects people in China and even across the globe, as it exhibits the highest rates of morbidity and mortality. Lung adenocarcinoma (LUAD) is a type of lung cancer with a very high incidence. The purpose of this study was to identify potential biomarkers that could be used to forecast the prognosis and improve the existing therapy options for treating LUAD. Clinical and RNA sequencing data of LUAD patients were retrieved from the TCGA database, while the mitochondria-associated gene sets were acquired from the MITOMAP database. Thereafter, Pearson correlation analysis was carried out to screen mitochondria-associated lncRNAs. Furthermore, univariate Cox and Lasso regression analyses were used for the initial screening of the target lncRNAs for prognostic lncRNAs before they could be incorporated into a multivariate Cox Hazard ratio model. Then, the clinical data, concordance index, Kaplan–Meier (K-M) curves, and the clinically-relevant subjects that were approved by the Characteristic Curves (ROC) were employed for assessing the model's predictive value. Additionally, the differences in immune-related functions and biological pathway enrichment between high- and low-risk LUAD groups were examined. Nomograms were developed to anticipate the OS rates of the patients within 1-, 3-, and 5 years, and the differences in drug sensitivity and immunological checkpoints were compared. In this study, 2175 mitochondria-associated lncRNAs were screened. Univariate, multivariate, and Lasso Cox regression analyses were carried out to select 13 lncRNAs with an independent prognostic significance, and a prognostic model was developed. The OS analysis of the established prognostic prediction model revealed significant variations between the high- and low-risk patients. The AUC-ROC values after 1, 3, and 5 years were seen to be 0.746, 0.692, and 0.726, respectively. The results suggested that the prognostic model riskscore could be used as an independent prognostic factor that differed from the other clinical characteristics. After analyzing the findings of the study, it was noted that both the risk groups showed significant differences in their immune functioning, immunological checkpoint genes, and drug sensitivity. The prognosis of patients with LUAD could be accurately and independently predicted using a risk prediction model that included 13 mitochondria-associated lncRNAs.

Effect of acoustic excitation on the combustion and emission characteristics of methane-ammonia-air swirling flame - Dongliang Wei; Hao Fang; Liubin Hu; Yan Rong; Hao Zhou (Fuel, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

Legume-based crop diversification reinforces soil health and carbon storage driven by microbial biomass and aggregates - Zhengjun Yan; Jie Zhou; Chunyan Liu; Rong Jia; Kevin Z. Mganga; Lei Yang; Yadong Yang; Leanne Peixoto; Huadong Zang; Zhaohai Zeng (Soil and Tillage Research, 2023)

Pogocablenes A-O, fifteen undescribed sesquiterpenoids with structural diversity from Pogostemon cablin - Shu-Yi Li; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Lu Su; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2023)

Experimental investigation of combustion and ash deposition characteristics of coal-NH3 cofiring in a 200 kW furnace - Shihao Hu; Yize Zhang; Yuguo Ni; Xinfeng Yu; Yan Rong; Kefa Cen; Hao Zhou (Fuel, 2023)

A GC/C/IRMS-based method for position-specific carbon isotopic analysis of saturated long chain fatty acids - Yu Zhao; Ran Ma; Yaoting Qi; Rong He; Zhenyu Zhu; Bo Wang; Ying Wang; Qiulin Yan; Maxime Julien; Youping Zhou (Organic Geochemistry, 2023)

The early Late Triassic Yumen mafic rocks in the eastern Tethyan Himalaya: A record of the progressive opening of the Yarlung Zangbo Neo-Tethyan Ocean - Wei-Liang Liu; Zhong-Xi Xia; Yun Zhong; Chris Yakymchuk; Zhou-Rong Cai; He Xiao; Xing Liao; Chi Yan; Ru-Xin Ding; Jin-Nan Liu (Lithos, 2023)

Solvent-freely polymerizing catechol and paraformaldehyde to nitrogen-rich carbon for high-volumetric-performance supercapacitor - Yushuai Yao; Rong Zhou; Yi Yu; Jian Chen; Cheng Du; Yan Zhang; Tao Long; Liu Wan; Qiuyue Wang; Mingjiang Xie (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Involvement of Abnormal p-α-syn Accumulation and TLR2-Mediated Inflammation of Schwann Cells in Enteric Autonomic Nerve Dysfunction of Parkinson’s Disease: an Animal Model Study - Wenwen Jiang; Yue Cheng; Ye Wang; Jing Wu; Zhe Rong; Li Sun; Yan Zhou; Kezhong Zhang (Molecular Neurobiology, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

HucMSC-EVs Facilitate In Vitro Development of Maternally Aged Preantral Follicles and Oocytes - Ying-Yi Zhang; Weijie Yang; Yi Zhang; Zhanhong Hu; Yingyan Chen; Yerong Ma; Anran Yang; Zhan Shi; Hanjing Zhou; Peipei Ren; Libing Shi; Jiamin Jin; et al. (Stem Cell Reviews and Reports, 2023)
Follicle developmental capacity and oocyte quality decline with advanced maternal age. Extracellular vesicles from human umbilical cord mesenchymal stem cells (HucMSC-EVs) act as a potential therapeutic product in the treatment of age-related ovarian dysfunction. In vitro culture (IVC) of preantral follicles is a useful method for understanding the mechanism of follicle development and is a promising means for improving female fertility. However, whether HucMSC-EVs have beneficial effects on aged follicle development during IVC has not yet been reported. Our research demonstrated that follicular development with single-addition withdrawal of HucMSC-EVs was better than that with continuous treatment with HucMSC-EVs. HucMSC-EVs facilitated the survival and growth of follicles, promoted the proliferation of granulosa cells (GCs), and improved the steroid hormone secretion of GCs during IVC of aged follicles. Both GCs and oocytes could uptake HucMSC-EVs. Moreover, we observed elevated cellular transcription in GCs and oocytes after treatment with HucMSC-EVs. The RNA sequencing (RNA-seq) results further validated that the differentially expressed genes are related to the promotion of GC proliferation, cell communication, and oocyte spindle organization. Additionally, the aged oocytes displayed a higher maturation rate, presented less aberrant spindle morphology, and expressed a higher level of the antioxidant protein Sirtuin 1 (SIRT1) after treatment with HucMSC-EVs. Our findings suggested that HucMSC-EVs can improve the growth and quality of aged follicles and oocytes in vitro through the regulation of gene transcription, which provides evidence for HucMSC-EVs as potential therapeutic reagents to restore female fertility with advanced age. Graphical Abstract

Conodont biostratigraphy and carbon isotope chemostratigraphy of the Middle to Upper Ordovician on the western Yangtze Platform, South China - Fang-Yi Gong; Guan-Zhou Yan; Rong-Chang Wu (Palaeoworld, 2023)

Relationships between Secreted Aspartyl Proteinase 2 and General Control Nonderepressible 4 gene in the Candida albicans resistant to itraconazole under planktonic and biofilm conditions - Wenli Feng; Jing Yang; Yan Ma; Luwen Zhang; Rong Yin; Zusha Qiao; Ying Ji; Yong’an Zhou (Brazilian Journal of Microbiology, 2023)

Virulence assessment of four Glaesserella parasuis strains isolated in Liaoning province of China - Ping Yan; Yong C. Jia; Xue L. Zhang; Yuan Y. Zhou; Ying Guo; Rong L. Yin; Jing Yuan; Lin X. Wang; Zhong B. Guo; Jing Y. Wang; Xin Wang; Rong H. Yin (Research in Veterinary Science, 2023)

A data driven method for multi-step prediction of ship roll motion in high sea states - Dan Zhang; Xi Zhou; Zi-Hao Wang; Yan Peng; Shao-Rong Xie (Ocean Engineering, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

A systematic analysis and evaluation of nutritional composition of 23 strains of marine microalgae commonly used in aquaculture - Jia-Xing Zhang; Zhao-Shou Ran; Hai-Xuan Xie; Fei Kong; Meng-Qi Zhang; Yao Zhou; Yan-Rong Li; Kai Liao; Xiao-Jun Yan; Ji-Lin Xu (Algal Research, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Biological magnetic ion exchange resin on advanced treatment of synthetic wastewater - Shanshan Xu; Yunbao Yan; Chendong Shuang; Qing Zhou; Rong Ji; Aimin Li (Bioresource Technology, 2023)

Spinal cord astrocyte P2X7Rs mediate the inhibitory effect of electroacupuncture on visceral hypersensitivity of rat with irritable bowel syndrome - Zhi-jun Weng; Shi-xiu Hu; Fang Zhang; Zhi-ying Zhang; Yun Zhou; Min Zhao; Yan Huang; Yu-hu Xin; Huan-gan Wu; Hui-rong Liu (Purinergic Signalling, 2023)

Erythropoietin promotes energy metabolism to improve LPS-induced injury in HK-2 cells via SIRT1/PGC1-α pathway - Kan Li; Li Gao; Sen Zhou; Yan-Rong Ma; Xiao Xiao; Qian Jiang; Zhi-Hong Kang; Ming-Long Liu; Tian-Xi Liu (Molecular and Cellular Biochemistry, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Adaptation of anammox consortia in microbial fuel cell to low temperature: Microbial community and predictive functional profiling - Geer An; Rong Yan; Zhimin Fu; Zepeng Chen; Yaru Guo; Jun Yang; Yongheng Zhou (Bioresource Technology, 2023)

Remodeled CD146+CD271+ Bone Marrow Mesenchymal Stem Cells from Patients with Polycythemia Vera Exhibit Altered Hematopoietic Supportive Activity - Chao Chen; Mingying Zhang; Rong Li; Jiajia Yuan; Jinqiang Yan; Yuhui Zhang; Wen Xing; Jie Bai; Yuan Zhou (Stem Cell Reviews and Reports, 2023)

Functional insights of a two-component system sensor kinase GacS in a fish pathogen, Pseudomonas plecoglossicida - Su-Ming Zhou; Yan Wang; Feng-Ling Shu; Zhen Tao; Xiao Xie; Jia-Song Xie; Rong-Rong Ma; Fei Yin (Aquaculture, 2023)

Iridoids and sesquiterpenoids from Valeriana officinalis and their bioactivities - Dao-Qun Shi; Jia-Jin Liu; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2023)

Hemin protects UVB-induced skin damage through inhibiting keratinocytes apoptosis and reducing neutrophil infiltration - Fang Bai; Chen Fan; Xi Lin; Hao-Yu Wang; Bing Wu; Chun-Lan Feng; Rong Zhou; Yan-Wei Wu; Wei Tang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Efficient synthesis of PdIr nanocatalysts with controllable surface composition for electrochemical oxidation of methanol - Ce Fu; Pan Wang; Rong-Hua Zhang; Luo-Yi Yan; Zheng Cheng; Xin Zhang; Xin-Wen Zhou (Fuel, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Exposure–response relationship between temperature, relative humidity, and varicella: a multicity study in South China - Yihan Li; Jialing Li; Zhihua Zhu; Weilin Zeng; Qi Zhu; Zuhua Rong; Jianxiong Hu; Xing Li; Guanhao He; Jianguo Zhao; Lihua Yin; Yi Quan; et al. (Environmental Science and Pollution Research, 2023)

Establishment of a novel myocarditis mouse model based on cyclosporine A - Tian Hao Zhao; Yi Xuan Jiang; Kai Qin Chen; Dan Qiu; Yan Zhe Xu; Chun Ye; Ting Ren; Bo Zhang; Bin Dai; Jue Hu; Jun Lu; Fang Liang Zhou; et al. (Genes & Genomics, 2022)

Similarity of the turbulent kinetic energy dissipation rate distribution in the upper mixed layer of the tropical Indian Ocean - Xian-Rong Cen; Shuang-Xi Guo; Yan Wang; Sheng-Qi Zhou (Frontiers in Marine Science, 2022)
Turbulence within the upper ocean mixed layer plays a key role in various physical, biological, and chemical processes. Between September and November 2011, a dataset of 570 vertical profiles of the turbulent kinetic energy (TKE) dissipation rate, as well as conventional hydrological and meteorological data, were collected in the upper layer of the tropical Indian Ocean. These data were used to statistically analyze the vertical distribution of the TKE dissipation rate in the mixed layer. The arithmetic-mean method made the statistical TKE dissipation rate profile more scattered than the median and geometric-mean methods. The statistical TKE dissipation rate were respectively scaled by the surface buoyancy flux and the TKE dissipation rate at the mixed-layer base. It was found that the TKE dissipation rate scaled by that at the mixed-layer base exhibited better similarity characteristics than that scaled by the surface buoyancy flux, whether the stability parameter D /| L MO | was greater or less than 10, indicating that the TKE dissipation rate at the mixed-layer base is a better characteristic scaling parameter for reflecting the intrinsic structure of the TKE dissipation rate in the mixed layer, where D and L MO are respectively the mixed-layer thickness and the Monin-Obukhov length scale. The parameterization of the TKE dissipation rate at the mixed-layer base on the shear-driven dissipation rate and the surface buoyancy flux was further explored. It was found that the TKE dissipation rate at the mixed-layer base could be well fitted by a linear combination of three terms: the wind-shear-driven dissipation rate, the surface buoyancy flux, and a simple nonlinear coupling term of these two .

The spatial-temporal consistency of chlorophyll-a and fishery resources in the water of the Zhoushan archipelago revealed by high resolution remote sensing - Lina Cai; Rong Tang; Xiaojun Yan; Yongdong Zhou; Jingjing Jiang; Menghan Yu (Frontiers in Marine Science, 2022)
Details of the chlorophyll- a (Chl- a ) distribution in the water of the Zhoushan archipelago were analyzed based on data from the panchromatic multispectral sensor (PMS) of the GaoFen-6 (GF-6). A new Chl- a inversion model was built using in-situ Chl- a and the green-red bands of the 2 m spatial resolution GF-6/PMS image. Combined with fishery data, the relationship between Chl- a concentration and fish resources were revealed. The results show that: (1) High Chl- a concentration area was mainly concentrated in the nearshore intensive islands waters, and Chl- a concentration changes obviously with the change of tidal currents. Chl- a concentration around islands increases, especially downstream of islands. Seasonally, Chl- a concentration is higher in spring and summer, lower in autumn, and lowest in winter. (2) The change of fish eggs and larvae in the water of the Zhoushan archipelago shows consistency with the spatial distribution and seasonal variation of Chl- a . (3) The interaction between tidal currents and islands results in the diverse currents (upstream upwelling and downstream vortex currents) around the islands, promoting vertical water exchange and the uplifting of nutrients, resulting in a high overall Chl- a concentration in the waters around the islands. The diverse flow conditions, the ideal nutrient-rich environment, and the abundant phytoplankton attract a large number of fish to gather and breed in the waters around the islands. (4) Chl- a of intensive island waters is an essential indicator for fish spawning grounds.

Optimization of the induction, germination, and plant regeneration system for somatic embryos in apomictic walnut (Juglans regia L.) - Hongcheng Fang; Yuhui Dong; Rui Zhou; Qingpeng Wang; Qicheng Duan; Changxi Wang; Yan Bao; Shengyi Xu; Xinya Lang; Shasha Gai; Rong Chen; Ke Qiang Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Effect of Fertilization Regimes and Seasonal Change on nosZ-Denitrifying Bacterial Community in a Double-Rice Paddy Field - Jiangwen Nie; Yong Zhou; Wei Yang; Shaoqiu Li; Haoxuan Li; Jianwei Wu; Chengwei Li; Xiaoyuan Yan; Rong Zhu; Bo Zhu; Zhangyong Liu (Journal of Soil Science and Plant Nutrition, 2022)

Preparation and In Vitro Characterization of Gelatin Methacrylate for Corneal Tissue Engineering - Yayun Yan; Yanyan Cao; Rong Cheng; Zhizhong Shen; Yajing Zhao; Yixia Zhang; Guohong Zhou; Shengbo Sang (Tissue Engineering and Regenerative Medicine, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Wisdom, predicaments, and challenges of a millennium ancient weir—Dujiangyan Project - Xiao-rong Huang; Xing-yu Zhou; Jin-jun You; Qing Yang; Yan-jun Wang; Kai Ma (Journal of Mountain Science, 2021)

Simultaneous detection of multiple bacterial and viral aquatic pathogens using a fluorogenic loop‐mediated isothermal amplification‐based dual‐sample microfluidic chip - Qian‐Jin Zhou; Jian‐Fei Lu; Xiu‐Rong Su; Jing‐Lei Jin; Shang‐Yang Li; Yan Zhou; Lei Wang; Xin‐Bin Shao; Yao‐Hua Wang; Mao‐Cang Yan; Ming‐Yun Li; Jiong Chen (Journal of Fish Diseases, 2021)
Rapid and user‐friendly diagnostic tests are necessary for early diagnosis and immediate detection of diseases, particularly for on‐site screening of pathogenic microorganisms in aquaculture. In this study, we developed a dual‐sample microfluidic chip integrated with a real‐time fluorogenic loop‐mediated isothermal amplification assay (dual‐sample on‐chip LAMP) to simultaneously detect 10 pathogenic microorganisms, that is Aeromonas hydrophila , Edwardsiella tarda , Vibrio harveyi , V. alginolyticus , V. anguillarum , V. parahaemolyticus , V. vulnificus , infectious hypodermal and haematopoietic necrosis virus, infectious spleen and kidney necrosis virus, and white spot syndrome virus. This on‐chip LAMP provided a nearly automated protocol that can analyse two samples simultaneously, and the tests achieved limits of detection (LOD) ranging from 10 0 to 10 –1 pg/μl for genomic DNA of tested bacteria and 10 –4 to 10 –5 pg/μl for recombinant plasmid DNA of tested viruses, with run times averaging less than 30 min. The coefficient of variation for the time‐to‐positive value was less than 10%, reflecting a robust reproducibility. The clinical sensitivity and specificity were 93.52% and 85.53%, respectively, compared to conventional microbiological or clinical methods. The on‐chip LAMP assay provides an effective dual‐sample and multiple pathogen analysis, and thus would be applicable to on‐site detection and routine monitoring of multiple pathogens in aquaculture.

Improvement and application of preprocessing technique for multitrace seismic impedance inversion - Zhong Fei-Yan; Zhou Lu; Dai Rong-Huo; Yin Cheng; Zhao Hu; Xu Liang-Jun (Applied Geophysics, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Water and salt stresses do not trigger bottom-up effects on plant-mediated indirect interactions between a leaf chewer and a sap-feeder - Yong-Cheng Dong; Zhi-Jian Wang; Rong-Yan Bu; Hui-Jie Dai; Li-Jun Zhou; Peng Han; Edwige Amiens-Desneux; Philippe Bearez; Nicolas Desneux (Journal of Pest Science, 2020)

Comparison of the effects of deep and moderate neuromuscular block on respiratory system compliance and surgical space conditions during robot-assisted laparoscopic radical prostatectomy: a randomized clinical study - Shao-jun Zhu; Xiao-lin Zhang; Qing Xie; Yan-feng Zhou; Kui-rong Wang (Journal of Zhejiang University-SCIENCE B, 2020)

Integrated fate assessment of aromatic amines in aerobic sewage treatment plants - Lin Jun Zhou; Zhi Yi Rong; Wen Gu; De Ling Fan; Ji Ning Liu; Li Li Shi; Yan Hua Xu; Zhi Ying Liu (Environmental Monitoring and Assessment, 2020)
The fate and exposure of chemicals in sewage treatment plants (STPs) are major considerations in risk assessment and environmental regulation. The biodegradability and removal of seven aromatic amines were systematically evaluated using a three-tiered integrated method: a standard ready biodegradability test, an aerobic sewage treatment simulation method, and model prediction. In tier 1, the seven aromatic amines were not readily biodegraded after 28 days. In adapted aerobic active sludge, 4-isopropyl aniline, 2,4-diaminotoluene, and 4-nitroaniline among them exhibited the degradation half-life time less than 20 h, the other four aromatic amines exhibited persistent with degradation half-life of > 60 h. In tier 2 of the aerobic sewage treatment simulation testing, 2,4-diaminotoluene, 4-nitroaniline, and 4-isopropylaniline demonstrated moderately to high overall removal. Hydraulic retention time (HRT) affects the removal with the optimum HRT was determined to be 12 h to 24. 2,6-Dimethyl aniline, 2-chloro-4-nitroaniline, 2,6-diethylaniline, and 3,4-dichloroaniline were not removed during the test, indicting these four aromatic amines will enter surface water and hence pose a potential risk to aquatic ecology. Considering the lack of an STP model in China for regulation purposes, in tier 3, we developed a Chinese STP (aerobic) (abbreviated as C-STP(O)) model that reflects a universal scenario for China to predict the fate. The predicted degradation, volatilization, and absorption showed a close relationship to the physicochemical properties of the chemicals, and had same tendency with tier 2 simulation test. The prediction showed that biodegradation rather than absorption or volatilization was the main removal process of aromatic amines in aerobic STP. With the combination of modified kinetics test with C-STP (O) model, the chemical fate can be more accurately predicted than using only the readily biodegradation result.

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Prenatal exposure to organophosphate pesticides, maternal paraoxonase 1 genotype, and childhood neurodevelopment at 24 months of age in Shandong, China - Yiwen Wang; Yan Zhang; Lin Ji; Yijun Zhou; Rong Shi; Michihiro Kamijima; Jun Ueyama; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2020)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

An integrated prevention strategy to address problems associated with continuous cropping of watermelon caused by Fusarium oxysporum - Fu-Yan Liu; Qiang Zhu; Hu-Rong Yang; Jun Zhou; Chuan-Chao Dai; Xing-Xiang Wang (European Journal of Plant Pathology, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

Recent advances in carbohydrate-based cancer vaccines - Ke-Tao Jin; Huan-Rong Lan; Xiao-Yi Chen; Shi-Bing Wang; Xiao-Jiang Ying; Yan Lin; Xiao-Zhou Mou (Biotechnology Letters, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Molecular, functional, and gene expression analysis of zebrafish Ror1 receptor - Yan Bai; Chengdong Liu; Jianfeng Zhou; Xiaozhi Rong; Hongying Wang (Fish Physiology and Biochemistry, 2019)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Late spring soil moisture variation over the Tibetan Plateau and its influences on the plateau summer monsoon - Juan Zhou; Jun Wen; Rong Liu; Xin Wang; Yan Xie (International Journal of Climatology, 2018)
Based on the European Centre for Medium‐Range Weather Forecasts (ECMWF) ERA‐Interim reanalysis data from 1979 to 2016, an index for Tibetan Plateau (TP) soil moisture ( I TPSM ), which could represent inter‐annual variation in spring soil moisture, is defined after removing the linear trend in soil moisture. The late spring soil moisture variation over the TP and its influences on the plateau summer monsoon are analysed. The results show that the TP soil moisture variation is non‐uniform, and spring soil moisture over the northeastern TP shows an increasing trend, while the western TP (especially the peripheral area) renders a significantly decreasing trend. When the I TPSM shows positive (negative) anomalies (i.e., spring soil moisture over the northeastern TP is higher (lower), soil moisture over the western TP is lower (higher) than normal), the plateau summer monsoon may be stronger (weaker). Anomalous variations in spring TP soil moisture can eventually affect the plateau summer monsoon by changing atmospheric circulation, diabatic heating, and water vapour transportation. It is found that when the I TPSM exhibits positive anomalies, diabatic heating over the centre and eastern TP is remarkably enhanced, and warm and humid moisture from the Bay of Bengal and Arabian Sea and cold air from high latitudes merge over the central and eastern TP; coupled with lower‐level convergence and upper‐level divergence, all these contribute to an increase in plateau summer monsoonal precipitation. When the I TPSM shows negative anomalies, diabatic heating over the centre and eastern TP is weakened, the anomalous cyclone to the south of the TP hinders warm and humid air flows transportation to the TP, and the anomalous anticyclone to the southeast of Lake Baikal weakens cold air to the south; coupled with weakened convergence and upwards motion, these factors all lead to a decrease in plateau summer monsoonal precipitation.

Genetic variability of wildlife-derived Sarcoptes scabiei determined by the ribosomal ITS-2 and mitochondrial 16S genes - Chun-Yan Li; Yin Sun; Yue Xie; Xuan Zhou; Xiao-Bin Gu; Wei-Ming Lai; Xue-Rong Peng; Guangyou Yang (Experimental and Applied Acarology, 2018)

Polybrominated diphenyl ethers in cord blood and perinatal outcomes from Laizhou Wan Birth Cohort, China - Limei Chen; Caifeng Wang; Yan Zhang; Yijun Zhou; Rong Shi; Chang Cui; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2018)

Linking intraspecific trait variability and spatial patterns of subtropical trees - En-Rong Yan; Liu-Li Zhou; Han Y. H. Chen; Xi-Hua Wang; Xiang-Yu Liu (Oecologia, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

DNA-Binding, Photocleavage, and Photodynamic Anti-cancer Activities of Pyridyl Corroles - Zhen-Hua Liang; Hai-Yang Liu; Rong Zhou; Zao Zhang; Atif Ali; Bing-Jie Han; Yun-Jun Liu; Xin-Yan Xiao (The Journal of Membrane Biology, 2016)

Prenatal low-level mercury exposure and infant neurodevelopment at 12 months in rural northern China - Yi Hu; Limei Chen; Caifeng Wang; Yijun Zhou; Yan Zhang; Yiwen Wang; Rong Shi; Yu Gao; Ying Tian (Environmental Science and Pollution Research, 2016)

Effects of silica exposure on the cardiac and renal inflammatory and fibrotic response and the antagonistic role of interleukin-1 beta in C57BL/6 mice - Jiali Guo; Tingming Shi; Xiuqing Cui; Yi Rong; Ting Zhou; Zhihong Zhang; Yuewei Liu; Yan Shen; Weihong Chen (Archives of Toxicology, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Household pesticide exposure and the risk of childhood acute leukemia in Shanghai, China - Yan Zhang; Yu Gao; Rong Shi; Didi Chen; Xiaojin Wang; Michihiro Kamijima; Kiyoshi Sakai; Tamie Nakajima; Md. Khalequzzaman; Yijun Zhou; Ying Zheng; Pingping Bao; et al. (Environmental Science and Pollution Research, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Trehalose Metabolism-Related Genes in Maize - Mei-Liang Zhou; Qian Zhang; Zhan-Min Sun; Li-Hui Chen; Bo-Xin Liu; Kai-Xuan Zhang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Journal of Plant Growth Regulation, 2014)

A Proteomic Analysis of Placental Trophoblastic Cells in Preeclampsia–Eclampsia - Kaidong Ma; Hong Jin; Rong Hu; Yu Xiong; Shufeng Zhou; Peng Ting; Yan Cheng; Yan Yang; Pengyuan Yang; Xiaotian Li (Cell Biochemistry and Biophysics, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

The role of HMGB1-RAGE axis in migration and invasion of hepatocellular carcinoma cell lines - Ruo-Chan Chen; Pan-Pan Yi; Rong-Rong Zhou; Mei-Fang Xiao; Ze-Bing Huang; Dao-Lin Tang; Yan Huang; Xue-Gong Fan (Molecular and Cellular Biochemistry, 2014)

Soluble N-terminal fragment of mutant Huntingtin protein impairs mitochondrial axonal transport in cultured hippocampal neurons - Jun Tian; Ya-Ping Yan; Rui Zhou; Hui-Fang Lou; Ye Rong; Bao-Rong Zhang (Neuroscience Bulletin, 2014)

Peroxisome Proliferator-Activated Receptor γ Ligands Retard Cultured Vascular Smooth Muscle Cells Calcification Induced by High Glucose - Ye-Bo Zhou; Jing Zhang; Ding-Qiong Peng; Jin-Rui Chang; Yan Cai; Yan-Rong Yu; Mo-Zhi Jia; Wei Wu; You-Fei Guan; Chao-Shu Tang; Yong-Fen Qi (Cell Biochemistry and Biophysics, 2013)

The association between CD14 gene C-260T polymorphism and coronary heart disease risk: a meta-analysis - Hong Pu; Jiong Yin; Yan Wu; Dongming Zhang; Yanian Wang; Rong Zhou; Lijuan Jiang; Yan Liu (Molecular Biology Reports, 2013)

Induction of annexin by heavy metals and jasmonic acid in Zea mays - Mei-Liang Zhou; Xiong-Bang Yang; Qian Zhang; Ming Zhou; En-Ze Zhao; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Nicotianamine synthase gene family as central components in heavy metal and phytohormone response in maize - Mei-Liang Zhou; Lei-Peng Qi; Jun-Feng Pang; Qian Zhang; Zhi Lei; Yi-Xiong Tang; Xue-Mei Zhu; Ji-Rong Shao; Yan-Min Wu (Functional & Integrative Genomics, 2013)

Musca Domestica Larva Lectin Induces Apoptosis in BEL-7402 Cells Through a Ca2+/JNK-mediated Mitochondrial Pathway - Chun-Ling Wang; Yan Xia; Jian-Zeng Nie; Minghui Zhou; Rong-Ping Zhang; Li-Li Niu; Li-Hua Hou; Xiao-Hong Cao (Cell Biochemistry and Biophysics, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Episodic orogeny deduced from coeval sedimentary sequences in the foreland basin and its implication for uplift process of Longmen Mountain, China - Yong Li; De-chen Su; Rong-jun Zhou; Hai-bing Li; Alexander L. Densmore; Liang Yan; Zhao-kun Yan (Journal of Mountain Science, 2013)

Formaldehyde Impairs Learning and Memory Involving the Disturbance of Hydrogen Sulfide Generation in the Hippocampus of Rats - Xiao-Qing Tang; Yuan-Yuan Zhuang; Ping Zhang; Heng-Rong Fang; Cheng-Fang Zhou; Hong-Feng Gu; Hui Zhang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2013)

Biomass accumulation and partitioning, photosynthesis, and photosynthetic induction in field-grown maize (Zea mays L.) under low- and high-nitrogen conditions - Jun-Wen Chen; Zhi-Qing Yang; Ping Zhou; Mei-Rong Hai; Tian-Xiang Tang; Yan-Li Liang; Tong-Xin An (Acta Physiologiae Plantarum, 2013)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

The role of leptin in lipid metabolism in fatty degenerated hepatocytes of the grass carp Ctenopharyngodon idellus - Rong-Hua Lu; Xu-Fang Liang; Min Wang; Yi Zhou; Xiao-Li Bai; Yan He (Fish Physiology and Biochemistry, 2012)

Aldehyde dehydrogenase protein superfamily in maize - Mei-Liang Zhou; Qian Zhang; Ming Zhou; Lei-Peng Qi; Xiong-Bang Yang; Kai-Xuan Zhang; Jun-Feng Pang; Xue-Mei Zhu; Ji-Rong Shao; Yi-Xiong Tang; Yan-Min Wu (Functional & Integrative Genomics, 2012)

A role for anti-CD45RB monoclonal antibody treatment upon dendritic cells - Hui Qi; Jin-Peng Liu; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2012)

Clinical characteristics of hepatitis B virus infection in middle school students born after the universal infant vaccination program in Shanghai, China - Wei-Ling Wang; Zhi-Jun Shu; Li-Xia Zhou; Yan-Rong Zhao (Archives of Virology, 2012)

Molecular cloning, characterization and expression of a chalcone reductase gene from Astragalus membranaceus Bge. var. mongholicus (Bge.) Hsiao - Rong-Yan Xu; Peng Nan; Haiyun Pan; Tongshui Zhou; Jiakuan Chen (Molecular Biology Reports, 2012)

PNAS-4 expression and its relationship to p53 in colorectal cancer - Bin Zhou; Hui Yan; Yuan Li; Rong Wang; Keling Chen; Zongguang Zhou; Xiaofeng Sun (Molecular Biology Reports, 2012)

Expressions of thermostable bacterial cellulases in tobacco plant - Xi-ran Jiang; Xiao-ya Zhou; Wen-yan Jiang; Xiao-rong Gao; Wen-li Li (Biotechnology Letters, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Sequence Analysis of the Lactoferrin Gene and Variation of g.7605C→T in 10 Chinese Indigenous Goat Breeds - Jing-Fen Kang; Xiang-Long Li; Hui-Qin Zheng; Rong-Yan Zhou; Lan-Hui Li; Hong-Yuan Zhao (Biochemical Genetics, 2011)

Methotrexate ameliorates pristane-induced arthritis by decreasing IFN-γ and IL-17A expressions - Wei-kun Hou; Lie-su Meng; Fang Zheng; Yu-rong Wen; Wen-hua Zhu; Cong-shan Jiang; Xiao-jing He; Yan Zhou; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2011)

Effects of erythromycin on voriconazole pharmacokinetics and association with CYP2C19 polymorphism - Hui-Yan Shi; Jin Yan; Wen-Hui Zhu; Guo-Ping Yang; Zhi-Rong Tan; Wei-Hua Wu; Gan Zhou; Xiao-Ping Chen; Dong-Sheng Ouyang (European Journal of Clinical Pharmacology, 2010)

Sequencing of Part of the Goat agouti Gene and SNP Identification - Xiang-long Li; Jing-wen Zhao; Chun-juan Tang; Rong-yan Zhou; Guiru Zheng; Lan-hui Li; Xiu-li Guo (Biochemical Genetics, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Erratum to: Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2009)

Temporal patterns of net soil N mineralization and nitrification through secondary succession in the subtropical forests of eastern China - En-Rong Yan; Xi-Hua Wang; Ming Guo; Qiang Zhong; Wu Zhou; Yong-Fu Li (Plant and Soil, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

An investigation on the polymorphisms of two DNA repair genes and susceptibility to ESCC and GCA of high-incidence region in northern China - Na Wang; Xiu-juan Dong; Rong-miao Zhou; Wei Guo; Xiao-juan Zhang; Yan Li (Molecular Biology Reports, 2009)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2008)

Passage number affects the pluripotency of mouse embryonic stem cells as judged by tetraploid embryo aggregation - Xiang-yun Li; Qing Jia; Ke-qian Di; Shu-min Gao; Xiao-hui Wen; Rong-yan Zhou; Wei Wei; Li-ze Wang (Cell and Tissue Research, 2007)

Rapid Detection of Avian Influenza Virus A and Subtype H5N1 by Single Step Multiplex Reverse Transcription-polymerase Chain Reaction - Hui-Ling Wei; Gui-Rong Bai; Aaron S. Mweene; Ying-Chun Zhou; Yan-Long Cong; Juan Pu; Shuai Wang; Hiroshi Kida; Jin-Hua Liu (Virus Genes, 2006)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

The role of CYP2C19 in amitriptyline N-demethylation in Chinese subjects - Zhi-Ping Jiang; Yan Shu; Xiao-Ping Chen; Song-Lin Huang; Rong-Hua Zhu; Wei Wang; Nan He; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

A novel human hydroxysteroid dehydrogenase like 1 gene (HSDL1) is highly expressed in reproductive tissuesa - Yan Huang; Rong Tang; Jianfeng Dai; Shaohua Gu; Wei Zhao; Chao Cheng; Ming Xu; Zongxiang Zhou; Kang Ying; Yi Xie; Yumin Mao (Molecular Biology Reports, 2001)

Cloning and Characterization of KLHL5, a Novel Human Gene Encoding a Kelch-Related Protein with a BTB Domain - Shu Wang; Zongxiang Zhou; Kang Ying; Rong Tang; Yan Huang; Chaoqun Wu; Yi Xie; Yumin Mao (Biochemical Genetics, 2001)

Detection of the organophosphorus nerve agent sarin by a competitive inhibition enzyme immunoassay - Yong-xin Zhou; Qing-jin Yan; Yun-xiang Ci; Zhen-quan Guo; Kang -Tai Rong; Wen-bao Chang; Yu-fen Zhao (Archives of Toxicology, 1995)